Pengaruh Tanggung Jawab Sosial Perusahaan terhadap Word of Mouth Elektronik PT Pegadaian yang Dimediasi oleh Citra Perusahaan dan Pengembangan Merek - Salwa Ramadhan; Sri Wahyuni (MAMEN: Jurnal Manajemen, 2026)
This research aims to explore the extent to which Corporate Social Responsibility (CSR) initiatives carried out by PT Pegadaian influence the community, encompassing both customers and non-customers, as reflected through the Word of Mouth variable. In addition, the study examines the mediating role of Corporate Image and Brand Development in the relationship between CSR and Word of Mouth. The sampling method applied is Non-Probability Sampling, where respondents are selected based on the researcher’s subjective judgment rather than randomization. Data collection employed a Likert scale to measure perceptions, while path analysis using the Partial Least Square (PLS) application was utilized to test the proposed model. The findings reveal that CSR significantly affects Word of Mouth, both directly and indirectly through Corporate Image and Brand Development. Hypothesis testing results indicate that seven hypotheses were accepted and one was rejected. These findings underscore the strategic importance of CSR not only as a social responsibility mechanism but also as a communication tool that strengthens corporate image and brand development. Ultimately, CSR contributes to building positive perceptions, enhancing brand communication, fostering community engagement, and increasing customer loyalty. This study highlights the role of CSR as a multidimensional driver that integrates social impact with marketing effectiveness, thereby reinforcing the sustainability and competitiveness of PT Pegadaian in the marketplace.